Strengthen PSNP Institutions and Resilience Phase II (SPIR II), Ethiopia: Group Problem Management Plus (g-PM+) Pilot Screening Survey - International Food Policy Research Institute (2023)
The study's objective is to estimate the impact of group Problem Management Plus (GPM+), with and without a lump-sum cash transfer, on mental health, daily activities, and economic outcomes among Productive Safety Net Program (PSNP) clients in the regions of Amhara and Oromia. The population for this study consists of individuals residing in Amhara and Oromia who are registered and assisted by the PSNP public works program. Moreover, to be eligible, individuals must show signs and symptoms of depression or dysfunction, be between 18 and 59 years old, and be the main decision-maker or spouse of the main decision-maker. The impact of GPM+ will be assessed through a two-stage cluster randomized control trial (cRCT) design.